American constitutional law - Kommers, Donald P. (West/Wadsworth, 1998)
AMERICAN CONSTITUTIONAL LAW presents a comprehensive look at the development of American constitutional law from its early, seminal Supreme Court cases (Marbury v. Madison) to the present. The comprehensive book is organized traditionally, beginning with governmental powers and concluding with civil rights and civil liberties. AMERICAN CONSTITUTIONAL LAW, VOLUME I, covers Chapters 1-7 of the comprehensive text dealing with the powers of the government: judicial review, regulating commerce, making treaties, etc